2020
DOI: 10.1101/2020.01.08.896290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rainbow Reporter Tracks Single Cells and Reveals Heterogeneous Cellular Dynamics among Pluripotent Stem Cells and their Differentiated Derivatives

Abstract: Recent single cell analyses have found molecular heterogeneities within populations of pluripotent stem cells (PSCs). A tool that tracks single cell lineages and their phenotypes longitudinally would reveal whether heterogeneity extends beyond molecular identity. Hence, we generated a stable Cre-inducible rainbow reporter human PSC line that provides up to 18 unique membrane-targeted fluorescent barcodes. These barcodes enable repeated assessments of single cells as they clonally expand, change morphology, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…To determine the long-term proliferative capacity of Tom + p16 high cells, we first labeled p16 high cells in 10-week-old mice by TAM treatment for 5 days and analyzed them 2 and 14 weeks after treatment. Given that prior cell tracing experiments clearly demonstrated that proliferating cells formed a cluster in tissues (Boone et al, 2019;El-Nachef et al, 2020;Ueno and Weissman, 2006), we examined whether Tom + p16 high cells formed clusters in the kidneys, lungs, and livers. We first partitioned all fields into squares with 25-fold larger average area of a targeted single Tom + p16 high cell and then calculated the number of Tom + p16 high cells in each square (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the long-term proliferative capacity of Tom + p16 high cells, we first labeled p16 high cells in 10-week-old mice by TAM treatment for 5 days and analyzed them 2 and 14 weeks after treatment. Given that prior cell tracing experiments clearly demonstrated that proliferating cells formed a cluster in tissues (Boone et al, 2019;El-Nachef et al, 2020;Ueno and Weissman, 2006), we examined whether Tom + p16 high cells formed clusters in the kidneys, lungs, and livers. We first partitioned all fields into squares with 25-fold larger average area of a targeted single Tom + p16 high cell and then calculated the number of Tom + p16 high cells in each square (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, hPSC-derived kidney organoids may represent an affordable model system for studying such dynamic processes in the human context. To this end, the combination of advanced imaging techniques together with hPSC reporter lines for the expression of key marker genes [61][62][63] and/or reporter systems for tracking of single cells and their progeny in an unbiased manner [64] will be crucial to monitor cellular behaviors at high spatiotemporal resolution. Additionally, techniques for spatiotemporal perturbation of relevant genetic, biochemical and mechanical effectors will be key to systematically test the interaction between these parameters [41,68].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Uniquely, hiPSC-CM reporter cells provide insights into human cardiogenesis without embryo donor requirements and without the concerns over species differences encountered with mouse models. Future multi-coloured reporter lines [ 46 ] may enable the discovery of novel cardiac progenitors, and the improvement of CM derivation and differentiation protocols.…”
Section: Psc-cm Reporter Lines: An Insight Into Cardiac Biologymentioning
confidence: 99%